OPTIMALISASI LAYANAN ADMINISTRASI PONDOK PESANTREN MELALUI SISTEM INFORMASI BERBASIS WEB MOBILE AL-HIDAYAH KALISARI, LAMPUNG TENGAH - Wahyu Sulistianing Budi; Siti Mukodimah (JECE (Journal of Ethics and Character Education), 2025)
This study aims to develop a mobile web–based information system to support service management at Pondok Pesantren Al-Hidayah, located in Kalisari, Kalirejo, Central Lampung. The system is designed to improve efficiency, accessibility, and service quality for students (santri), administrators, and other stakeholders. The development process follows several stages, including requirements analysis, system design, implementation, and testing. By adopting mobile web technology, the system enables users to access information and utilize various services anytime and anywhere through their mobile devices. The proposed system integrates key features such as institutional profile information, activity schedules, announcements, financial information, and new student registration. In addition, communication features are provided to facilitate interaction between students, pesantren administrators, and parents or guardians through instant messaging or notification services. These features aim to reduce manual administrative processes, minimize information delays, and enhance transparency in service delivery. The results of this study indicate that the developed system has the potential to significantly improve operational efficiency and user experience in pesantren services. Furthermore, this system can serve as a foundational platform for future development, particularly in expanding the integration of information technology to support daily operational and managerial activities within Islamic boarding schools